2008
DOI: 10.1016/s1472-6483(10)60246-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of symptomatic uterine leiomyoma with letrozole

Abstract: Uterine leiomyomas are the most common benign tumours of the female genital tract, often necessitating hysterectomy. The most common symptoms are dysmenorrhoea, menorrhagia, infertility and abortion. Ovarian hormones seem to play an essential role in pathogenesis, and deprivation of ovarian oestrogen causes leiomyomas to shrink significantly. The purpose of this study was to evaluate the effects of the non-steroidal aromatase inhibitor letrozole on uterine leiomyomas and on bone metabolism. A prospective, open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 38 publications
1
27
0
2
Order By: Relevance
“…17 Gurates et al reported that at the end of 3 month, letrozole resulted in a mean 46.72% reduction of original uterine leiomyoma volume and mean reduction of original uterine volume by 21.67% whereas Hilario SG et al reported that there was average reduction of uterine volume of 9.32% attaining up to 30% with the use of anastrazole 1 mg/day over 12 weeks. 8,12 This study also demonstrated an increase in the haemoglobin concentration which may be due to an improved menstrual pattern. Baseline mean value of haemoglobin concentration was 9.59±1.26 g/dl and at the end of treatment it was 10.76±0.85 g/dl and hence statistically significant (p <0.01).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…17 Gurates et al reported that at the end of 3 month, letrozole resulted in a mean 46.72% reduction of original uterine leiomyoma volume and mean reduction of original uterine volume by 21.67% whereas Hilario SG et al reported that there was average reduction of uterine volume of 9.32% attaining up to 30% with the use of anastrazole 1 mg/day over 12 weeks. 8,12 This study also demonstrated an increase in the haemoglobin concentration which may be due to an improved menstrual pattern. Baseline mean value of haemoglobin concentration was 9.59±1.26 g/dl and at the end of treatment it was 10.76±0.85 g/dl and hence statistically significant (p <0.01).…”
Section: Discussionsupporting
confidence: 56%
“…Deprivation of ovarian oestrogen causes leiomyoma to shrink. 8 Some investigators have shown that leiomyoma tissues are a source of oestrogen. Oestrogen secreted by leiomyomatous tissue may reach a sufficient concentration within the local compartment to support its own growth.…”
Section: Introductionmentioning
confidence: 99%
“…Letrozole, a selective, competitive, reversible non-steroidal aromatase inhibitor decreases the volume of myomas and the intensity of associated symptoms [7][8][9][10][11]. Ulipristal acetate (UPA), a selective progesteronereceptor modulator, decreases the volume of uterine myomas and controls uterine bleeding [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Aromatase inhibitors, including letrozole, anastrozole, and fadrozole, are a class of agents that block the synthesis of estrogen. Aromatase inhibitors have been shown to readily reduce UF size (up to 71% in 2 months) 82 and ameliorate UF symptoms, including a reduction in menstrual volume and duration of menstruation, and urinary retention [82][83][84] . The most common side effects of aromatase inhibitors include hot flashes, vaginal dryness, and musculoskeletal pain 14 .…”
Section: Future Optionsmentioning
confidence: 99%